STRATEGY OF ENHANCING THE COMPETITIVESS OF LEATHER’S SMEs : STUDY IN MANDING YOGYAKARTA - Ninik Sri Rahayu; Khusniyah Purwani (UII, 2012)
The majority of the Manding’s leather manufacturers are small medium entreprise (SME), with limited productive resources. The paper try to identify problems of leather’s manufacturers and formulate strategy to enhance their competitiveness in domestic and overseas market. Most of the SMEs have characteristic as follow : utilization of old manufacturing processes, traditional management, low labor productivity poor intelligence and information systems on trade and marketing, rarely work with other firms, have no development activities, lack of technology adoption, and hardly ever bring new products on the market which lead their product being uncompetitive in market. To attain the competitiveness, SMEs need to consider some of the principle strategies, first, the innovation strategy, in which SMEs try to appropriate returns from their knowledge base. Second, the information technology strategy, which makes innovative uses of information technology in order to reduce SME costs and increase productivity. Third, the network strategy, in which SMEs work and co-operate with other firms, be they SMEs or large enterprises in order to improve their ability to access and absorb innovations. Fourth, the cluster strategy, in which SMEs locate in close proximity with competitors in order to take advantage of knowledge spill- overs, especially in the early stages of the industrial lifecycle. Keywords: Competitiveness, innovation strategy, information technology strategy,network strategy, cluster strategy